The crosstalk between MYC and mTORC1 during osteoclastogenesis - Bae, Seyeon; Oh, Brian; Tsai, Jefferson; Park, Peter Sang Uk; Greenblatt, Matthew Blake; Giannopoulou, Eugenia G.; Park-Min, Kyung-Hyun (Frontiers in Cell and Developmental Biology, 2022)
Osteoclasts are bone-resorbing cells that undergo extensive changes in morphology throughout their differentiation. Altered osteoclast differentiation and activity lead to changes in pathological bone resorption. The mammalian target of rapamycin (mTOR) is a kinase, and aberrant mTOR complex 1 (mTORC1) signaling is associated with altered bone homeostasis. The activation of mTORC1 is biphasically regulated during osteoclastogenesis; however, the mechanism behind mTORC1-mediated regulation of osteoclastogenesis and bone resorption is incompletely understood. Here, we found that MYC coordinates the dynamic regulation of mTORC1 activation during osteoclastogenesis. MYC-deficiency blocked the early activation of mTORC1 and also reversed the decreased activity of mTORC1 at the late stage of osteoclastogenesis. The suppression of mTORC1 activity by rapamycin in mature osteoclasts enhances bone resorption activity despite the indispensable role of high mTORC1 activation in osteoclast formation in both mouse and human cells. Mechanistically, MYC induces Growth arrest and DNA damage-inducible protein (GADD34) expression and suppresses mTORC1 activity at the late phase of osteoclastogenesis. Taken together, our findings identify a MYC-GADD34 axis as an upstream regulator of dynamic mTORC1 activation in osteoclastogenesis and highlight the interplay between MYC and mTORC1 pathways in determining osteoclast activity.